ENHANCED SEMI-EMPIRICAL THERMODYNAMIC MODEL FOR CARBON DIOXIDE SOLUBILITY IN AQUEOUS ALKANOLAMINES - SULEMAN, HUMBUL (2016)
Phase equilibrium studies play a pivotal role in equipment design, system integration and process development by establishing process boundaries and operational scope of a chemical system. Most of experimental studies are not expansible to industrial environments due to their highly nonlinear nature and carbon dioxide-alkanolamine-water system is no exception. Hence, a thermodynamic approach is mandatory to correlate the process variables with good concocti~m of simplicity, accuracy and efficiency.